Possible Protective Effects of Lutein against Ciprofloxacin Induced Bone Marrow Toxicity in Rats - Khudhair, Alaa R.; Al-Shawi, Nada N (Iraqi Journal of Pharmaceutical Sciences, 2021)
Ciprofloxacin, which is a second generation of fluoroquinolone and one of the most effective and widely used drugs within fluoroquinolone. Unfamiliar adverse effects of ciprofloxacin such as bone marrow (BM) suppression, thrombocytopenia, anemia, agranulocytosis, renal failure, and others observed. Lutein, is a xanthophyll (an oxygenated carotenoid), was focused by most studies as it has a strong antioxidant activity in vitro; and also, it has been associated with reducing the risk of the age-related disorders. The current study was designed to describe the role of apoptosis through the measurement of Bcl-2 associated X protein (Bax) marker, as mechanisms of bone marrow toxicity induced by ciprofloxacin and to find whether lutein may have protective effects on ciprofloxacin-induced toxicity in bone marrow of rats. Ciprofloxacin (Group II) caused significant (P<0.05) reduction in total RBCs counts and -WBCs, and significantly elevations (P<0.05) Bcl-2 associated X protein (Bax) in bone marrow (BM) tissues homogenates compared to control (Group I) rats.